X2 - 5X - 4 = 0
X = - b (+/-) sqrt(b2 - 4ac)/2a
a = 1
b = - 5
c = - 4
X = - ( - 5) (+/-) sqrt[(- 5)2 - 4(1)(- 4)]/2(1)
X = 5 (+/-) sqrt(25 + 16)/2
X = [5 (+/-) sqrt(41)]/2
-------------------------------------exact answer
Chat with our AI personalities
Using the quadratic equation formula:- x = 3.795831523 or x = -5.795831523
If: x2+x = 12 Then: x2+x-12 = 0 And using the quadratic formula: x = -4 or x = 3
By using the quadratic equation formula: (4x+1)(x-3) = 0
In the generic formula, replace the coefficients a = 1, b = -2, c = -3.
If you can't factor it easily, use the quadratic formula.